How Do Banks Determine Their Capital Buffer? Evidence from Indonesian Bank - Mahendra Ryansa Gallen Gagah Pratama; Tyas Effendi; Lina Nur Hidayati; Alfonso Mendoza-Velázquez (Journal of Management and Entrepreneurship Research, 2021)
Objective: This study aims to investigate how banks determine their capital buffer. Return on Equity (ROE), Non-Performing Loans (NPL), Capital Buffer Lag (BUFFt-1), Loan to Total Assets (LOTA), and Income Diversification (IDIV) are some of the variables examined in this study. Research Design & Methods: Purposive sampling was used to collect samples for this study. It was 20 of the 42 conventional commercial banks that were listed on the Indonesia Stock Exchange in 2012-2016. In this study, multiple regression analysis was used, as well as the ordinary and two-stage least squares methods. Findings: The results of this study have shown that the capital buffer has a negative impact on return on equality (ROE) and income diversification (IDIV). The capital buffer was affected by Lag of Capital Buffer. This research examines how a bank can make a profit from the negative impact of ROE. Based on the results of the tests, the Indonesian Bank has not pursued the highest possible capital buffer. Implications & Recommendations: Companies will use their profit to further profitable activities when they fulfill a minimum capital buffer requirement. Contribution & Value Added: The results of this study try to give an idea for the management of capital and capital buffers and to determine the ideal strategy for investors and banks to meet the Basel and Government regulation. This research tries to add insight into the internal factors that determine capital buffers at conventional commercial banks in Indonesia, as well as research references in the field of financial management, particularly capital buffers.